The Length-Length Relationships, Growth Pattern and Condition of Rasbora sp. in Tamblingan Lake, Bali Island - I Nyoman Yoga Parawangsa; Prawira A.R.P. Tampubolon; Nyoman Dati Pertami (Warmadewa University Press, 2022)
Rasbora sp. is one of native fish species that inhabit in Tamblingan Lake. Several publication that discussed about this species in other ecosystem was published, but very rare information in Tamblingan Lake. The aims of this research ware determine the length-length relationships, growth pattern and condition Rasbora sp. in Tamblingan Lake. Fish sampling conducted from January to December 2019 in Tamblingan Lake. The sampling method was purposive sampling which did alternately every month on five sampling station that representing the condition of Tamblingan Lake. The result shown, all character of length has strong correlation with body weight of fish, but the total length (TL) was the most accurate measure to estimating the body weight of Rasbora sp. The growth pattern of Rasbora sp. was isometric and the condition of this fish in good condition.